2001
DOI: 10.1007/s001670100212
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of tunnel dilation on the mechanical properties of hamstring grafts fixed in the tibia with interference screws

Abstract: The effect of dilation of the tibial tunnel on the strength of hamstring graft fixation using interference screws was evaluated. In all, 28 RCI screws were tested in male human tibia-hamstring constructs with tibial tunnels reamed or dilated to the respective size of the graft diameter. Dilation of the tibial tunnel failed to significantly enhance hamstring fixation. Grafts secured in dilated tunnels displayed an 11% greater resistance to the initiation of graft slippage (174+/-112 N) compared to their undilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
32
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 24 publications
5
32
0
1
Order By: Relevance
“…They concluded that using an anatomical fixation with stiff and strong fixation devices combined with a less aggressive rehabilitation program could contribute to minimizing tunnel enlargement after ACL reconstruction with doubled hamstrings. Other reported series with different time periods showed the increase in the width of the tunnels from 6 weeks up to 2 years [5,12,20,21]. In the current study, measurements of tunnel diameters taken in a follow-up period after 2 years were found in similar ranges to reported series in the literature (Table 1).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…They concluded that using an anatomical fixation with stiff and strong fixation devices combined with a less aggressive rehabilitation program could contribute to minimizing tunnel enlargement after ACL reconstruction with doubled hamstrings. Other reported series with different time periods showed the increase in the width of the tunnels from 6 weeks up to 2 years [5,12,20,21]. In the current study, measurements of tunnel diameters taken in a follow-up period after 2 years were found in similar ranges to reported series in the literature (Table 1).…”
Section: Discussionsupporting
confidence: 88%
“…The investigators yielded in both studies significantly higher graft pull-out values for the dilated tibial specimens than for the reamed specimens with mechanical testing [1][2][3]. Rittmeister et al's study [21] concluded that the benefit of dilators was related to a better match of tunnel and graft size, than achieving good bone quality. Arnoczky et al [1] have demonstrated insertion torque and pullout strength are increased by compaction drilling.…”
Section: Discussionmentioning
confidence: 99%
“…Our small specimen number and low statistical power preclude making a definitive conclusion that differences do not truly exist. Many previous reports, 39,46,51 as well as this study, have had low statistical power creating a high likelihood of type II error, precluding the ability to firmly conclude that tunnel wall dilation does not indeed improve soft tissue tendon graft fixation. Our lack of performing an a priori statistical power analysis is a study limitation.…”
Section: Discussionmentioning
confidence: 79%
“…There are a lot of reports on different methods of femoral and tibial graft fixation and its mechanical properties [9,14]. However, there are few works on technical or mechanical complications.…”
Section: Discussionmentioning
confidence: 99%